Effect of the Chinese New Year Public Holiday on the Glycemic Control of T1DM With Intensive Insulin Therapy - Guo, Keyu; Ye, Jianan; Zhang, Liyin; Tian, Qi; Fan, Li; Ding, Zhiyi; Zhou, Qin; Li, Xia; Zhou, Zhiguang; Yang, Lin (Frontiers in Endocrinology, 2022)
Aims There is limited evidence that evaluates the glycemic control of type 1 diabetes mellitus (T1DM) during the Chinese New Year public holiday in China. The Chinese New Year public holiday represents various challenges to glycemic control, especially in T1DM patients, in China. We aimed to assess the effect of the Chinese New Year public holiday on several glucose metrics using flash glucose monitoring (FGM) in patients with T1DM. Methods Complete FGM data for 1 week before, 1 week during and 1 week after the Chinese New Year public holiday were available for 71 T1DM patients treated with multiple daily insulin injection (MDI) therapy (n = 51) or continuous subcutaneous insulin infusion (CSII) treatment (n = 20). The mean age of the study participants was 13 (9, 30) years. Of note, 59.2% of the patients (n = 42) were adults, and 40.8% of the patients (n = 29) were minors. The interval between each two adjacent periods was one week. The indicators of mean glucose, glucose variability and time in different glycemic ranges were analyzed. Results The Chinese New Year public holiday was associated with an increase in mean blood glucose (8.2 ± 1.9 vs. 8.9± 2.8; P < 0.001) and time above range (TAR) (26.1% ± 18.1% vs. 31.7% ± 23.9%; P < 0.001) but a decrease in time in range (TIR) (65.7% ± 16.8% vs. 59.9% ± 21.1%; P < 0.001) and coefficient of variation (CV) (38.2% ± 8.2% vs. 36.7% ± 7.7%; P =0.037). There was no statistically significant difference in time below range (TBR). The glycemic control deteriorated during the Chinese New Year public holiday in our study population regardless of age. Interestingly, in the CSII group, none of the metrics of glucose control significantly changed during the Chinese New Year public holiday. Conclusions These results suggested that less self-management may worsen glycemic control in the short term, indicating a need for more refined management algorithms during the Chinese New Year public holiday for T1DM patients.